2020
DOI: 10.1002/csc2.20143
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of spike fruiting efficiency in wheat

Abstract: Spike fruiting efficiency (FE), defined as grains per unit of spike dry weight at anthesis (SDWa) is a promising trait for improving grain number (GN) in wheat (Triticum aestivum L.). It is often estimated at maturity as the grains per unit of chaff or FE at maturity (FEm). The fertile floret efficiency (FFE), defined as fertile florets per unit of SDWa, and grain set (GST), or the number of grains per floret, were studied to better understand FE determination for the first time. Two double haploid populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Each spikelet contains 8–12 florets and produces usually 3–5 grains per spikelet 1 . Important determinants of grain number are the floret fertility 4 as well as spike fruiting efficiency (grains per unit spike dry weight at anthesis) 5 , 6 . Among the complex network of spike-related traits, total spikelet number per spike (TSN) was studied in several reports.…”
Section: Introductionmentioning
confidence: 99%
“…Each spikelet contains 8–12 florets and produces usually 3–5 grains per spikelet 1 . Important determinants of grain number are the floret fertility 4 as well as spike fruiting efficiency (grains per unit spike dry weight at anthesis) 5 , 6 . Among the complex network of spike-related traits, total spikelet number per spike (TSN) was studied in several reports.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no conclusive results of how accurate SF at maturity is in estimating SF at anthesis, Slafer et al (2015) suggest that there are indications of a small overestimation of the SF at maturity, due to the fact that spike dry matter may increase from anthesis to maturity. In this respect, Pretini et al (2020a) observed instability in this estimator in different environments. However, Abbate et al (2013) found high association between these two indices (r > 0.7), and Alonso et al (2018), Fischer and Rebetzke (2018), and Pradhan et al (2019) detected a positive association between SF at maturity and NG.…”
Section: Introductionmentioning
confidence: 87%
“…Abbate et al (2013) proposed the alternative of the spike fertility index measured at maturity (i.e., calculated with spike chaff weight at maturity), as a selection criterion in breeding programs. This trait has been then shown to have good association with NG (Alonso et al 2018, Pradhan et al 2019) and moderate to MP Alonso et al high heritability (Martino et al 2015, Alonso et al 2018, Pretini et al 2020a, as well as transgressive segregation and a low genotype × environment interaction (Martino et al 2015, Mirabella et al 2016, Alonso et al 2018).…”
Section: Introductionmentioning
confidence: 98%
“…This would explain the high importance in GN and FF determination of: (i) the spike dry weight achieved at anthesis (SDW) [ 10 , 12 , 61 , 62 ]; and (ii) the dry matter partitioned within the spike between florets/grains and spike structure parts, i.e. the fertile floret efficiency (FFE, fertile florets per g of SDW) [ 63 ] and the fruiting efficiency (FE, grains per g of SDW, or FEm grains per g of chaff at maturity) [ 15 , 63 68 ]. It has been reported that in modern elite cultivars the SDW was less important to explain GN variation than the fruiting efficiency [ 15 , 63 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…the fertile floret efficiency (FFE, fertile florets per g of SDW) [ 63 ] and the fruiting efficiency (FE, grains per g of SDW, or FEm grains per g of chaff at maturity) [ 15 , 63 68 ]. It has been reported that in modern elite cultivars the SDW was less important to explain GN variation than the fruiting efficiency [ 15 , 63 69 ]. The GST is considered to be high in relative modern cultivars (i.e., > 80% of fertile florets set grains) [ 10 , 67 , 70 ], but it has been recently shown that it can be as low as 60% [ 45 , 63 ].…”
Section: Introductionmentioning
confidence: 99%